Pengembangan Keterampilan Partisipasi Sosial Melalui Pembelajaran Ips Terpadu Kota Pekanbaru, Riau - Nurmansyah Nurmansyah; Emilia Susanti; Dessy Fitria Nastiti; Labibah Azzahra; Muhammad Al Habib; Nurhasanah Nurhasanah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The aim of this research is to increase social participation among students through learning Social Sciences (IPS). Participation in social activities is an important part of education because it prepares people to engage effectively in society. The research method used was classroom action (PTK) involving class VII students in one of the junior high schools in city X. The research process was divided into two stages, each through four stages: planning, implementation, observation and reflection. Data collection was carried out by observation, questionnaires, interviews and documentation, then analyzed quantitatively. This study found that social studies education can significantly increase students' social participation. Employees' ability to communicate and collaborate is used as a sign of progress.